(untitled) (Journal of the College of Basic Education, 2022)
The current research aimed at measuring fear among adolescent students and the significance of differences in it according to the variables of age and gender.The sample of the current research consisted of (200) male and female adolescents equally from middle school students in the city of Baghdad, on its two sides, Karkh and Rusafa, at ages (14,13,12) years.The researcher adopted the Sharia scale (2007) to measure fear among adolescents after adapting it to the Iraqi environment, and she presented it to a group of experts in educational and psychological sciences. They are: test-retest and Cronbach’s alpha